2023
DOI: 10.1101/2023.03.07.531463
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systematic review on leptospirosis in cattle: a European perspective

Abstract: Background: Leptospirosis is a zoonotic disease which is globally distributed. Bovine leptospirosis often results in economic losses through its severe impact on reproduction performance. However, a clear overview of the disease characteristics in European cattle is lacking. The objective of this review was to summarise the current knowledge and state of the research on the epidemiology of bovine leptospirosis in Europe. Methodology: We conducted a systematic literature review following the PRISMA guidelines. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 118 publications
0
1
0
Order By: Relevance
“…Although serological evaluations typically return a higher prevalence for leptospirosis than isolation or PCR [ 28 , 39 , 48 , 49 , 50 , 51 ], we concluded that serological evaluations do not accurately estimate active infection or carrier status, and they may not demonstrate pathogen shedding [ 49 , 50 , 51 ]. Optimizing the isolation protocol for Leptospira spp.…”
Section: Discussionmentioning
confidence: 99%
“…Although serological evaluations typically return a higher prevalence for leptospirosis than isolation or PCR [ 28 , 39 , 48 , 49 , 50 , 51 ], we concluded that serological evaluations do not accurately estimate active infection or carrier status, and they may not demonstrate pathogen shedding [ 49 , 50 , 51 ]. Optimizing the isolation protocol for Leptospira spp.…”
Section: Discussionmentioning
confidence: 99%